The Education and Counseling for Scabies Prevention: Edukasi Dan Konseling Guna Pencegahan Scabies - Setyorini, Andri; Lutifah , Rahmiyati (Ruang Ide Publisher, 2022)
Abstract Background: Scabies is a contagious skin infection disease caused by a type of tick. Scabies disease ranks 3 of the 12 most common skin diseases in Indonesia. The high prevalence of scabies is generally found in environments with high population density and interpersonal contacts such as prisons, orphanages, and Islamic boarding schools. Improving knowledge and attitudes of students can be done by providing health education with appropriate and effective learning methods. A person's knowledge and attitude certainly has a role to play in prevention by practicing good personal hygiene to prevent the occurrence of scabies, besides that someone can also know about what factors cause scabies.Activity: This activity is Education and Counseling for Scabies Prevention given to Santri at Al I'tishom Islamic Boarding School Gunung Kidul Yogyakarta. Objective: To increase the knowledge and attitudes of students in scabies prevention behavior. Method of Implementation: The implementation of this community service is carried out online using goo meet in 3 sessions, namely: Session 1: Education about Scabies Disease; Session 2: Counseling and Sharing by involving student companions (ustadz); Session 3: Evaluation. Conclusion: More than 50% of the participants were able to answer the post-test questions correctly orally; 100% of the assistants are active in providing assistance to students during the implementation of education and are also active in discussions during counseling. Suggestion: After this education and counseling has been carried out, the students should be able to further improve their clean and healthy attitudes and behavior in order to prevent scabies. And boarding school administrators are expected to further improve education, especially about scabies disease and make a periodic supervision schedule to find out earlier the possibility of scabies events in students. Keywords: Education, Counseling, Scabies, Students